Edukasi Fisioterapi Komunitas untuk Meningkatkan Pengetahuan Carpal Tunnel Syndrome pada Pekerja Kantor Kutai Barat - Dewi Sawitri; Atika Yulianti (Health Care : Journal of Community Service, 2025)
One of the work-related musculoskeletal diseases is Carpal Tunnel Syndrome (CTS), which is a common occupational health problem among workers who frequently perform tasks involving prolonged hand use and improper positioning. CTS occurs when the median nerve is compressed at the wrist, causing paresthesia, numbness, and muscle weakness in the hand. The purpose of this educational session was to increase knowledge and awareness regarding the prevention and management of Carpal Tunnel Syndrome through physiotherapy exercises that can be performed independently by office workers. The methods included education on the definition, prevalence, risk factors, symptoms, and self-managed physiotherapy exercises, using leaflets and PowerPoint slides as educational media. The results of the physiotherapy education session conducted at the Department of Education and Culture of Kutai Barat showed an improvement in workers’ knowledge about Carpal Tunnel Syndrome and the physiotherapy exercises that can be performed independently